2021
DOI: 10.48550/arxiv.2110.03444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symmetry Classification and Universality in Non-Hermitian Many-Body Quantum Chaos by the Sachdev-Ye-Kitaev Model

Antonio M. García-García,
Lucas Sá,
Jacobus J. M. Verbaarschot

Abstract: Spectral correlations are a powerful tool to study the dynamics of quantum many-body systems. For Hermitian Hamiltonians, quantum chaotic motion is related to random matrix theory spectral correlations. Based on recent progress in the application of spectral analysis to non-Hermitian quantum systems, we show that local level statistics, which probes the dynamics around the Heisenberg time, of a non-Hermitian q-body Sachdev-Ye-Kitev (nHSYK) model with N Majorana fermions, and its chiral and complex-fermion exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…In generic (i.e., chaotic) closed manybody quantum systems, interactions may entail such a complex structure that the Hamiltonian behaves in several aspects like a large random matrix, as conjectured by Bohigas, Giannoni, and Schmit [4]. Extending this result to the dissipative realm is a fundamental problem that has attracted considerable attention recently [5][6][7][8][9][10][11]. Along similar lines, the past couple of years have seen the development of the (non-Hermitian) random matrix theory of Lindbladian dynamics [12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…In generic (i.e., chaotic) closed manybody quantum systems, interactions may entail such a complex structure that the Hamiltonian behaves in several aspects like a large random matrix, as conjectured by Bohigas, Giannoni, and Schmit [4]. Extending this result to the dissipative realm is a fundamental problem that has attracted considerable attention recently [5][6][7][8][9][10][11]. Along similar lines, the past couple of years have seen the development of the (non-Hermitian) random matrix theory of Lindbladian dynamics [12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 98%
“…Moreover, several experimental implementations have been proposed [65][66][67][68][69][70] and its practical and technological relevance has been highlighted [71][72][73][74][75][76]. Finally, non-Hermitian SYK models have also started gaining traction, with studies focusing on thermodynamics and wormhole physics [77,78], symmetries and universality [11], entanglement dynamics [79,80], and the effect of decoherence on quantum chaos [81,82].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, based on the symmetry classes of Dirac operators [27], a classification of non-Hermitian random matrices was undertaken [28], that was recently revisited [29] and leads to 38 classes. Half of these classes have been identified in a non-Hermitian Sachdev-Ye-Kitaev model [30]. Based on heuristic arguments and numerics, it was found that only three distinct classes of 2D bulk statistics exist [15]: The Ginibre ensemble [6] and two further classes labelled AI † and AII † (in analogy to [26]), that possess additional symmetries under transposition.…”
mentioning
confidence: 99%